DAMPAK POLA ASUH SINGLE PARENT TERHADAP PERKEMBANGAN KEPRIBADIAN ANAK DI KAMPUNG PASIR KALAPA RT 02 DESA CIBIUK KECAMATAN CIRANJANG KABUPATEN CIANJUR - Sarah, Siti Sarah Rahmayanti; Ansori, Ansori; Widiastuti, Novi (Comm-Edu (Community Education Journal), 2025)
Single parents are people who raise their children alone, without help from their parents. They have significant responsibilities when it comes to raising their family. Single-parent families have more serious problems than single-parent families. This is largely due to the need for extra care and attention to ensure that the child is not abused in any situation. This research uses qualitative methodology. The sampling technique used in this research is purposive sampling, namely samples selected with certain considerations and objectives. Research findings show that very few solitary parents raise their children according to their own wishes. Therefore, the way one presents oneself to others has a significant impact on a child's behavior. If the way they present themselves to others is not appropriate, children can become introverted or extroverted. There are several types of parenting styles that parents can give to children, namely as follows: (1) Democratic Parenting Pattern (2) Authoritarian Parenting Pattern (3) Permissive Parenting Pattern.